Early modern French thought the age of suspicion - Moriarty, Michael, 1956- (Oxford University Press, 2003)
This text is an examination of three major French thinkers of the 17th century, Descartes, Pascal and Malebranche. It examines their critical accounts of the impact of the body and of social relationships on experience, and the need to correct this by reference to metaphysical or religious truth.